2013
DOI: 10.1007/s00540-013-1689-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delayed extubation in thoracic and lumbar spine surgery: a retrospective analysis of 135 patients

Abstract: Our study suggests that intraoperative factors including prolonged surgical time, significant blood loss, larger volume of crystalloid and colloid infusion, and blood transfusion may be risk factors for delayed extubation following thoracic or lumbar spine surgery. Early blood transfusion may also increase the risk of delayed extubation. Patient factors did not affect extubation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Epstein and Dexter (2013) investigated the relationship between prolonged extubation and OR cost, and concluded that prolonged extubation time should be treated as resulting in proportionally increased variable costs [32]. In addition, 55.6% of the cases with prolonged extubation occurred during cases on regular workdays and in an OR with more than eight hours of cases and turnover [32,33]. Another study conducted by the same group demonstrated that the mean time from end of surgery to exit from the OR was at least 12.6 minutes longer in cases with prolonged extubation, and that the percentage of cases for which the extubation was prolonged (among anesthesia for intraperitoneal procedures in the lower abdomen) was 13.3% ± 0.5% [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epstein and Dexter (2013) investigated the relationship between prolonged extubation and OR cost, and concluded that prolonged extubation time should be treated as resulting in proportionally increased variable costs [32]. In addition, 55.6% of the cases with prolonged extubation occurred during cases on regular workdays and in an OR with more than eight hours of cases and turnover [32,33]. Another study conducted by the same group demonstrated that the mean time from end of surgery to exit from the OR was at least 12.6 minutes longer in cases with prolonged extubation, and that the percentage of cases for which the extubation was prolonged (among anesthesia for intraperitoneal procedures in the lower abdomen) was 13.3% ± 0.5% [7].…”
Section: Discussionmentioning
confidence: 99%
“…These factors included prone position, prolonged surgical time, significant blood loss, larger volume of crystalloid and colloid infusion, procedure, and surgeon [7,33]. Lai and Chan (2015) reported that DES anesthesia, longer anesthesia time, higher BMI, and shorter surgical time contribute to slower emergence in gynecologic laparoscopic surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…There were studies that investigated the confounding risk factors of prolonged extubation which included prone position, prolonged surgical time, significant blood loss, and larger volume of crystalloid and colloid infusion. [ 6 , 26 , 27 ] Our previous study reported that DES anesthesia, lengthy anesthesia time, higher BMI, and shorter surgical time contribute to slower emergence in gynecologic laparoscopic surgery. [ 14 ] In addition, Chan et al [ 19 ] demonstrated that the confounding factors that predicted awaken under TCI with propofol are age, gender, and times of surgery and anesthesia (total consumption dose of propofol and fentanyl) in assortments of surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we did not include patients receiving Whipple operation and blood loss >1500 mL because larger volume of fluid infusion may be the risk factor for delayed extubation. [ 26 ] Finally, we did not use BIS in our common practice. But the depth of anesthesia was monitored by the experienced anesthesiologist, and our percentage of prolonged extubation was 9.6% less than overall 15.4% reported by a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors of prolonged extubation including prone position, prolonged surgical time, significant blood loss, larger volume of crystalloid and colloid infusion, procedure, or surgeon. [ 20 , 24 ] In addition, more than half of the cases with prolonged extubation occurred during cases on regular workdays and in an OR with >8 hours of cases and turnover. [ 23 ] The result was consisted with the previous reports, as we showed prolonged extubation was associated with anesthetic and surgical time.…”
Section: Discussionmentioning
confidence: 99%